Inhibition of allogeneic inflammatory responses by the Ribonucleotide Reductase Inhibitors, Didox and Trimidox - Inayat, Mohammed S (BioMed Central, 2010)
BACKGROUND: Graft-versus-host disease is the single most important obstacle facing successful allogeneic stem cell transplantation (SCT). Even with current immunosuppressive therapies, morbidity and mortality rates are high. Current therapies including cyclosporine A (CyA) and related compounds target IL-2 signaling. However, although these compounds offer great benefit, they are also associated with multiple toxicities. Therefore, new compounds with a greater efficacy and reduced toxicity are needed to enable us to overcome this hurdle. METHODS: The allogeneic mixed lymphocyte reaction (MLR) is a unique ex vivo method to study a drug's action on the initial events resulting in T-cell activation and proliferation, synonymous to the initial stages of tissue and organ destruction by T-cell responses in organ rejection and Graft-versus-host disease. Using this approach, we examined the effectiveness of two ribonucleotide reductase inhibitors (RRI), Didox and Trimidox, to inhibit T-cell activation and proliferation. RESULTS: The compounds caused a marked reduction in the proliferative responses of T-cells, which is also accompanied by decreased secretion of cytokines IL-6, IFN-γ, TNF-α, IL-2, IL-13, IL-10 and IL-4. CONCLUSIONS: In conclusion, these data provide critical information to justify further investigation into the potential use of these compounds post allogeneic bone marrow transplantation to alleviate graft-versus-host disease thereby achieving better outcomes.